A new 3D phase unwrapping method by region partitioning and local polynomial modeling in abdominal quantitative susceptibility mapping - Cheng, Junying; Song, Manli; Xu, Zhongbiao; Zheng, Qian; Zhu, Li; Chen, Wufan; Feng, Yanqiu; Bao, Jianfeng; Cheng, Jingliang (Frontiers in Neuroscience, 2023)
Manuscript body Word count: 272 (abstract), 3851 (body), 4 (figures), 1(table ) 1 The authors are accountable for all aspects of the work in ensuring that questions related to the accuracy or integrity of any part of the work are appropriately investigated and resolved. The study was conducted in accordance with the Declaration of Helsinki (as revised in 2013). The study was approved by ethics board of the First Affiliated Hospital of Zhengzhou University (No.: 2018-KY-88) and informed consent was taken from all the patients.